Inferring a difference in the star-forming properties of lower versus higher X-ray luminosity AGNs. (28th November 2018) - Bernhard, E; Grimmett, L P; Mullaney, J R; Daddi, E; Tadhunter, C; Jin, S
ABSTRACT: We explore the distribution of R MS ≡ SFR/SFRMS (where SFRMS is the star formation rate of 'main-sequence' star-forming galaxies) for AGN hosts at z = 1. We split our sample into two bins of X-ray luminosity divided at L X = 2 × 10 43 erg s −1 to investigate whether the R MS distribution changes as a function of AGN power. Our main results suggest that, when the R MS distribution of AGN hosts is modelled as a log-normal distribution (i.e. the same shape as that of MS galaxies), galaxies hosting more powerful X-ray AGNs (i.e. L X > 2 × 10 43 erg s −1 ) display a narrower R MS distribution that is shifted to higher values compared to their lower L X counterparts. In addition, we find that more powerful X-ray AGNs have SFRs that are more consistent with that of MS galaxies compared to lower L X AGNs. Despite this, the mean SFRs (as opposed to R MS ) measured from these distributions are consistent with the previously observed flat relationship between SFR and L X . Our results suggest that the typical star-forming properties of AGN hosts change with L X, and that more powerful AGNs typically reside in more MS-like star-forming galaxies compared to lower L X AGNs.